Treatment of Acutely Ruptured Cerebral Aneurysms With the Woven EndoBridge (WEB) Flow Disruptor: A Multicenter Experience. (1st September 2019) - Saiegh, Fadi Al; Hasan, David M; Mouchtouris, Nikolaos; Zanaty, Mario; Chalouhi, Nohra; Ghosh, Ritam; Sweid, Ahmad; Tjoumakaris, Stavropoula I; Gooch, M Reid; Rosenwasser, Robert H; Jabbour, Pascal
Abstract: INTRODUCTION: Coiling has become the first-line treatment option for acutely ruptured aneurysms 1 to 3. However, coiling of wide-necked bifurcation aneurysms is challenging and stent-assisted coiling requires dual anti-platelet therapy. The Woven EndoBridge (WEB) flow disruptor has been recently Food and Drug Administration (FDA)-approved for bifurcation aneurysms and is designed to achieve intrasaccular flow diversion without the need for antiplatelet therapy. However, its use has been mostly reserved for unruptured aneurysms. Here, we present our series of ruptured aneurysms that were treated with the WEB-device post FDA approval. METHODS: We performed a review of the first cohort of patients with acute subarachnoid hemorrhage (SAH) from ruptured aneurysms who underwent endovascular treatment with the WEB-device at Thomas Jefferson and Iowa University Hospitals and identified 7 patients. RESULTS: All 7 patients were female and the mean age was 71 yr (range 57-81). Hunt and Hess grades ranged from 2 to 5. The aneurysms treated included anterior communicating, posterior communicating, posterior-inferior cerebellar (PICA), basilar apex, and vertebrobasilar junction (VBJ). In 6 of the 7 aneurysms, 1 WEB device was sufficient to achieve adequate obliteration; the VBJ aneurysm was 14 mm in size and required 2. The majority of patients underwent treatment via transfemoral access followed by transradial. One patient underwent direct carotid puncture due to vessel tortuosity. Aneurysm rebleeding was not encountered in any of the WEB-treated aneurysms. One patient had an intraoperative rupture of their PICA aneurysm after dislodgment of the WEB device. There were no treatment-related deaths, but one patient died of cardiopulmonary failure. CONCLUSION: Our series shows that the WEB device can be safely used in ruptured bifurcation aneurysms of various sizes in the anterior and posterior circulation. It does not require adjunctive stent use and is a valuable alternative to stent-assisted coiling as it obviates the need for anti-platelet therapy.